Transcriptional addiction in cancer cells is mediated by YAP/TAZ through BRD4 - Zanconato, Francesca; Battilana, Giusy; Forcato, Mattia; Filippi, Letizia; Azzolin, Luca; Manfrin, Andrea; Quaranta, Erika; Biagio, Daniele Di; Sigismondo, Gianluca; Guzzardo, Vincenza; Lejeune, Pascale; Haendler, Bernard; et al. (Nature medicine, 2018)
Cancer cells rely on dysregulated gene expression. This establishes specific transcriptional addictions that may be therapeutically exploited. Yet, the mechanisms that are ultimately responsible for these addictions are poorly understood. Here, we investigated the transcriptional dependencies of transformed cells to the transcription factors YAP and TAZ.